Dynamics of an algae–bacteria microcosm: Photosynthesis, chemotaxis, and expulsion in inhomogeneous active matter - Praneet Prakash; Yasa Baig; François J. Peaudecerf; Raymond E. Goldstein (Proceedings of the National Academy of Sciences, 2025)
In nature, there are significant relationships known between microorganisms from two kingdoms of life, as in the supply of vitamin B 12 by bacteria to algae. Such interactions motivate general investigations into the spatiotemporal dynamics of metabolite exchanges. Here we study by experiment and theory a model system: a coculture of the bacterium Bacillus subtilis , an obligate aerobe that is chemotactic to oxygen, and a nonmotile mutant of the alga Chlamydomonas reinhardtii , which photosynthetically produces oxygen when illuminated. Strikingly, when a shaft of light illuminates a thin, initially uniform suspension of the two, the chemotactic influx of bacteria to the photosynthetically active region leads to expulsion of the algae from that area. We propose that this effect arises from advection by the inhomogeneous bacterial concentration. The resulting generalization of Fick’s law has been proposed in the context of chemotaxis and is mathematically related to the “turbulent pumping” in magnetohydrodynamics.